Tendencje rozwojowe na rynku mięsa w Polsce - Kozłowski, Wojciech (Development Tendency on the Meat Market in Poland, 2006)
The objective of the paper is to determine the changes which have appeared on the potential meat market in Poland from the beginning of the 90s. In order to obtain the aim, an attempt is made to determine the demand, prices and market potential of meat. As a result of the observed changes the structure of meat market and the potential of markets are changing considerably to the advantage of raw poultry meat.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 477-483